2021
DOI: 10.3390/ijms22179506
|View full text |Cite
|
Sign up to set email alerts
|

Isoleucilactucin Ameliorates Coal Fly Ash-Induced Inflammation through the NF-κB and MAPK Pathways in MH-S Cells

Abstract: We investigated whether isoleucilactucin, an active constituent of Ixeridium dentatum, reduces inflammation caused by coal fly ash (CFA) in alveolar macrophages (MH-S). The anti-inflammatory effects of isoleucilactucin were assessed by measuring the concentration of nitric oxide (NO) and the expression of pro-inflammatory mediators in MH-S cells exposed to CFA-induced inflammation. We found that isoleucilactucin reduced CFA-induced NO generation dose-dependently in MH-S cells. Moreover, isoleucilactucin suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…Furthermore, IF staining revealed that CFA increased the p-NF- κ B translocation in the nucleus, whereas PBE (100 μ g/mL) and Bay-11 (10 μ M) significantly decreased the p-NF- κ B translocation from the cytoplasm to the nucleus ( Figure 5 ). A similar result was also found in our previous study [ 19 , 34 ]. Bay-11 has been reported to have an anti-inflammatory activity that inhibits the phosphorylation of I κ B [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, IF staining revealed that CFA increased the p-NF- κ B translocation in the nucleus, whereas PBE (100 μ g/mL) and Bay-11 (10 μ M) significantly decreased the p-NF- κ B translocation from the cytoplasm to the nucleus ( Figure 5 ). A similar result was also found in our previous study [ 19 , 34 ]. Bay-11 has been reported to have an anti-inflammatory activity that inhibits the phosphorylation of I κ B [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…These pro-inflammatory mediators activate the cascade of pro-inflammatory cytokines, including IL-1β, IL-6, and TNF-α. Notably, these 3 cytokines may be harmful to their cells if their release is not effectively inhibited [36]. This notion is further confirmed by our results (Figs.…”
Section: Mh-s Cells No/inflammationsupporting
confidence: 87%
“…As a fundamental biological process, inflammation is the protective response to tackle invading pathogens, antigens or damaged cells or tissues. It provides a defence mechanism to eliminate harmful substances and perform tissue repair [ 14 , 15 ]. At the molecular and cellular level, inflammation is characterized by five major signs: redness, heat, pain, swelling and functional loss.…”
Section: Mechanisms Of Inflammationmentioning
confidence: 99%
“…IκB will be further phosphorylated to lead activation of NF-κβ. Taken together, both signalling pathways play an important role in the inflammatory processes because they are the suppliers of proinflammatory cytokines and thus serve as targets for drug action [ 15 , 21 , 36 ].…”
Section: Mechanisms Of Inflammationmentioning
confidence: 99%